A NEW MULTIPLICATIVE INVERSE SUM INDEG INDEX OF CERTAIN BENZENOID SYSTEMS - Kulli, V.R. (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
In this paper, we introduce a new topological index: first multiplicative inverse sum indeg index of a molecular graph. We compute the inverse sum indeg index and first multiplicative inverse sum indeg index of triangular benzenoid, benzenoid rhombus and benzenoid hourglass. Keywords: inverse sum indeg index, multiplicative inverse sum indeg index, benzenoid. Mathematics Subject Classification: 05C05, 05C12.